Growth of onion (Allium cepa L.) var. "Red Arequipeña" due to fertilization NxK - Amaya Robles, Julio Estuardo (2012)
Whit the objective to determining the influence of increasing levels of nitrogen and potassium in the growth of onion, was carried an experiment in Pampas de San Juan, Laredo during October 2010 to January 2011. We used certified seed red onion var. "Red Arequipeña". The treatments were the combinations results of 60, 120, 180 and 240 kg N ha-1 and 40, 80 and 160 kg K2O ha-1, used as a single dose, 80 kg P2O5 ha-1. The experiment was designed in randomized complete block with 3x4 factorial arrangements with three replications. The results of this research to conclude that the dose of 120 kg N.ha-1, was obtained a linear response to nitrogen ascendant of 44.9cm in height with 90 days of DDT and 14.2 mm for diameter of the false stem with 60 N.kg-1 to 104 days DDT. There were no responses to potassium in this variable. There were no responses to NxK for the number of leaves.